Kualitas Tidur Buruk Pada Pasien Riwayat Stroke Iskemik di Palembang - Adinda Tsaltsabila Putri,; Dian Wahyuni; Karolin Adhisty (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2023)
Stroke is the second leads of death and the third leads of disability in adults in the world. Ischemic stroke cases are the most common cases of stroke. In addition to mortality problems, ischemic stroke can also cause other problems such as poor sleep quality. This research aims to show and describes the quality of sleep based on the seven components of sleep quality in patients with history of ischemic stroke at Siti Fatimah Az-Zahra Hospital, South Sumatra. This research is a quantitative descriptive study with 33 respondents who are patients with history of ischemic stroke in the Outpatient Room. The sample of this study is taken by using a purposive sampling technique. The research data is collected by using the PSQI (Pittsburgh Sleep Quality Index) questionnaire. The results shows that 84.8% has poor sleep quality and an overview of each component shows that the majority of respondents felt that their sleep quality is quite poor, they took ?15 hours to fall asleep, can fall asleep only <5 hours, has sleep efficiency <65%. , has sleep disturbances 2 times a week, most of respondents never use sleeping pills and most of respondents has activity disturbances during the day. In conclusion, the majority of patients with history of ischemic stroke in Regional Hospital Palembang have poor sleep quality. Good or poor sleep quality is determined by the seven components of sleep quality. if it occurs continuously can affect the quality of life of patients with history of ischemic stroke, so further attention and consideration is needed